Upaya Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pembelajaran Matematika Materi Perbandingan Trigonometri dengan Pendekatan Contextual Teaching and Learning (CTL) Di Kelas X MA Nurul Cholil Bangkalan - Hendaryono, Satokit (Jurnal Simki Pedagogia, 2023)
This study aims to implement mathematics learning with the CTL approach on trigonometry comparison material in order to improve the critical thinking skills of class X students of MA Nurul Cholil Bangkalan. This research is a classroom action research. This research was carried out learning mathematics with the Contextual Teaching and Learning (CTL) approach on the subject matter of trigonometry comparisons. The research subjects were class X students while the object of research was the whole process and results of learning mathematics using the Contextual Teaching and Learning (CTL) approach. The research instrument was in the form of observation sheets on the implementation of learning, field notes, final tests of cycle I and cycle II. The results showed that CTL learning using reference to the seven main components of effective learning, which consists of: constructivism, asking, finding, learning communities, modeling, reflection, and actual assessment of trigonometry comparison material can improve the critical thinking skills of class X students of MA Nurul Cholil Bangkalan. Based on the results of the analysis of the final cycle test, in cycle I the average score of students' critical thinking skills achieved was 56% in poor qualifications then increased in cycle II to 85% in good qualifications. In addition, the number of students who scored critical thinking skills in good qualifications increased from cycle I to cycle II.